Inoculation with a microbial consortium increases soil microbial diversity and improves agronomic traits of tomato under water and nitrogen deficiency - Cirillo, Valerio; Romano, Ida; Woo, Sheridan L.; Di Stasio, Emilio; Lombardi, Nadia; Comite, Ernesto; Pepe, Olimpia; Ventorino, Valeria; Maggio, Albino (Frontiers in Plant Science, 2023)
Microbial-based biostimulants, functioning as biotic and abiotic stress protectants and growth enhancers, are becoming increasingly important in agriculture also in the context of climate change. The search for new products that can help reduce chemical inputs under a variety of field conditions is the new challenge. In this study, we tested whether the combination of two microbial growth enhancers with complementary modes of action, Azotobacter chroococcum 76A and Trichoderma afroharzianum T22, could facilitate tomato adaptation to a 30% reduction of optimal water and nitrogen requirements. The microbial inoculum increased tomato yield (+48.5%) under optimal water and nutrient conditions. In addition, the microbial application improved leaf water potential under stress conditions (+9.5%), decreased the overall leaf temperature (-4.6%), and increased shoot fresh weight (+15%), indicating that this consortium could act as a positive regulator of plant water relations under limited water and nitrogen availability. A significant increase in microbial populations in the rhizosphere with applications of A. chroococcum 76A and T. afroharzianum T22 under stress conditions, suggested that these inoculants could enhance soil microbial abundance, including the abundance of native beneficial microorganisms. Sampling time, limited water and nitrogen regimes and microbial inoculations all affected bacterial and fungal populations in the rhizospheric soil. Overall, these results indicated that the selected microbial consortium could 2 This is a provisional file, not the final typeset article function as plant growth enhancer and stress protectant, possibly by triggering adaptation mechanisms via functional changes in the soil microbial diversity and relative abundance.